THE POWER OF POLITICAL INVESTORS IN THE VILLAGE HEAD ELECTION IN MADURA - Mohammad Hidayaturrahman; Hisyamuddin Moh. Syah; Ida Syafriyani; Ahmad Hasan Ubaid (Journal of Governance Innovation, 2023)
Democracy in Indonesia is much broader than democracy in developed countries such as America and Europe. This can be seen from the democracy practiced in Indonesia down to the village level. Village head elections have been carried out directly for generations. Public participation in the village head election is also the highest of all existing contestations. Political participation of village residents continues to grow. One form of participation that brings problems is the involvement of political funders known as political investors in village head elections. This research was conducted to determine the role of political investors in village head elections in Sumenep, Madura, East Java. The research used descriptive qualitative methods and data collection techniques using in-depth interviews with informants who were directly involved in village head election activities. In addition, document searches were carried out regarding activities related to the election of village heads and the relationship between village head candidates and political investors. This research reveals the important role of investors in winning village head candidates. Political investors receive compensation for the funding provided, in the form of positions for families in village governments that have been funded. Apart from that, political investors receive economic benefits in the form of village projects and village land management rights. This research has limitations at the location scale, which only covers three villages in Sumenep Regency, Madura.